Music and facial emotion recognition and its relationship with alexithymia - García-Rodríguez, María; Alvarado, Jesús M.; Fernández Company, José Fernando; Jiménez, Virginia; Ivanova-Iotova, Anelia (Psychology of Music, 2023)
The objective of this study was to determine the influence of alexithymia on the ability to identify emotions through visual and auditory stimuli. We assessed Alexithymia using the Toronto Alexithymia Scale (TAS-20). As visual stimuli, we employed the images of faces from the Ekman 60 Faces Test, while the auditory stimuli consisted of fragments of instrumental music. A total of 303 students participated, 139 in secondary education and 164 in the first year of university (M = 17.58 years; SD = 4.16). The results show higher alexithymia levels in the female participants than in the male participants, mainly in the difficulty identifying feelings (DIF) and difficulty describing feelings (DDF) factors, and higher in the secondary students than in the university students, especially in externally oriented thinking (EOT). In terms of the identification of emotions through auditory stimuli, the EOT factor showed a strong predictive effect for the emotions of surprise and anger. For the visual stimuli, the EOT factor showed predictive validity for identifying happiness, while the DDF factor showed predictive validity for identifying sadness. We conclude that there is a relationship between alexithymia levels and emotion recognition, which varies depending on the nature of the stimulus.
Keywords: adolescence; alexithymia; emotion perception; facial visual stimuli; music; Scopus; JCR